Kepuasan pengguna Market Place Shopee yang ditinjau dari aspek Word of Mouth dan pengalaman konsumen - Novita Butarbutar; Marto Silalahi; Julyanthry Julyanthry; Acai Sudirman (Universitas Darussalam Gontor, 2020)
The development of information technology has changed all aspects of human life, particularly the habit of using information technology to meet every day needs. One of the concrete matters that we can see from the rapid development of information technology is the behavior of using marketplaces to carry out online shopping, which is currently increasingly popular to use by consumers. This study aimed to determine how much the influence of price and word of mouth on consumer satisfaction. Data obtained from the research objects were analyzed using a survey model with a quantitative approach. The number of samples obtained as respondents was 160 people. Data for analysis used validity and reliability tests using the outlier model and the SEM structural model as a representative of the inner model. The results of the study show that word of mouth has no effect on user satisfaction. Furthermore, the consumer experience has a significant effect on user satisfaction.